The macroeconomic and microeconomic factors of residential property prices in Nusajaya - Yusoff, Nurul Nabilah (2019)
Although there is excess supply and a lot of unsold homes and a bubble market, every year the price of residential property market showed an increase especially in major urban areas in Malaysia such as the Klang Valley, Penang and Johor. Therefore, the purpose of this case study research was to explore the movement for residential property prices and to determine the macroeconomic and microeconomic factors affecting residential property in Nusajaya. This qualitative exploration was to determine macroeconomic and microeconomic factors of residential property prices in Nusajaya by collecting interview data from a sample of 7 participants consisting of developers and government agencies. Text and content analyses were used to analyse the interview transcripts, and other primary documents to provide a full extent of the macroeconomic and microeconomic for residential property prices movement coverage. The précis of the analysis signified that the property price is gradually increasing in Nusajaya. The macroeconomic factors such as construction cost, demographic factor and property speculation affect the most in the increasing of residential property prices in Nusajaya. Whilst for the microeconomic factors such as physical factor, locational and accessibility factor affect the most in the movement of residential property prices in Nusajaya. Therefore, this study revealed that the macroeconomic and microeconomic driver is the key factor affecting the price movement of residential property in Nusajaya.